Inhibition of Activin Receptor Type IIB Increases Strength and Lifespan in Myotubularin-Deficient Mice - Lawlor, Michael W. (American Society for Investigative Pathology, 2011)
X-linked myotubular myopathy (XLMTM) is a congenital disorder caused by deficiency of the lipid phosphatase, myotubularin. Patients with XLMTM often have severe perinatal weakness that requires mechanical ventilation to prevent death from respiratory failure. Muscle biopsy specimens from patients with XLMTM exhibit small myofibers with central nuclei and central aggregations of organelles in many cells. It was postulated that therapeutically increasing muscle fiber size would cause symptomatic improvement in myotubularin deficiency. Recent studies have elucidated an important role for the activin-receptor type IIB (ActRIIB) in regulation of muscle growth and have demonstrated that ActRIIB inhibition results in significant muscle hypertrophy. To evaluate whether promoting muscle hypertrophy can attenuate symptoms resulting from myotubularin deficiency, the effect of ActRIIB-mFC treatment was determined in myotubularin-deficient (Mtm1δ4) mice. Compared with wild-type mice, untreated Mtm1δ4 mice have decreased body weight, skeletal muscle hypotrophy, and reduced survival. Treatment of Mtm1δ4 mice with ActRIIB-mFC produced a 17% extension of lifespan, with transient increases in weight, forelimb grip strength, and myofiber size. Pathologic analysis of Mtm1δ4 mice during treatment revealed that ActRIIB-mFC produced marked hypertrophy restricted to type 2b myofibers, which suggests that oxidative fibers in Mtm1δ4 animals are incapable of a hypertrophic response in this setting. These results support ActRIIB-mFC as an effective treatment for the weakness observed in myotubularin deficiency.